Safety and efficacy of clonazepam in patients with hemifacial spasm: A double-blind, randomized, placebo-controlled trial. (October 2022) - Baek, Seol-Hee; Shin, Je-Young; Sohn, Sung-Yeon; Park, Kee Hong; Kim, Jun-Soon; Kim, Bongjae; Ahn, So Hyun; Choi, Kyomin; Hong, Yoon-Ho; Sung, Jung-Joon
Abstract: Introduction: Hemifacial spasm (HFS) is an involuntary intermittent twitching of the facial muscles. Medical and surgical treatments can be considered for HFS. Among medical treatments, clonazepam is a benzodiazepine used to treat epilepsy, psychiatric symptoms, and movement disorders. This study aimed to investigate the efficacy and safety of clonazepam for the treatment of HFS. Methods: This randomized double-blind placebo-controlled trial prospectively enrolled patients with HFS aged 20–79 years. The patients were randomly assigned in a 1:1 ratio to receive either clonazepam (0.5 mg twice daily) or a placebo for 4 weeks. All participants underwent clinical assessment and laboratory tests at baseline and visit 2. The primary endpoint was the clinical global impression-improvement (CGI-I) score at visit 2. Results: A total of 34 patients with HFS assessed for eligibility were enrolled between April 2015 and November 2016. Among them, two patients were withdrawn before randomization. Thus, the intention-to-treat analysis included 32 patients with HFS. The median CGI-I scores at visit 2 did not differ significantly between the clonazepam (3; range 1–6) and placebo (3.5; range 3–5) groups. In the safety analysis, only mild or no serious adverse events were observed. Conclusion: The results of this study demonstrated the safety of clonazepam in patients with HFS. However, clonazepam did not show a statistically significant effect on HFS. Further studies are needed to provide evidence of the clinical benefits in patients with HFS. Highlights: This study is the first double-blind, randomized, placebo-controlled trial on the efficacy and safety of clonazepam in hemifacial spasm (HFS). This study did not demonstrate the significant efficacy of clonazepam in HFS. This study has revealed that clonazepam is relatively safe in HFS.